Overview of Country Experience in Land Rights and Developmental Statehood: South Korea, Taiwan, China and Singapore - Stebek, EN (Mizan law review, 2014)
This article examines lessons that can be drawn from the land rights regimes of four countries that have commendable economic performance. It highlights the nature of land rights during the developmental statehood pursuits of three East Asian states (South Korea, Taiwan and Singapore) and a country that currently pursues socialist market economic policy, i.e. China. The themes that are considered include (a) lessons from the land rights regime in South Korea including the salient features of  developmental states, (b) Taiwan’s land reform during the early 1950s and land requisition for industrial use, (c) China’s land rights regime and administrative laws, and (d) land rights in Singapore and entrepreneur perceptions about its institutions. These countries are chosen due to their relevance to the Ethiopian land law regime. The article highlights how South Korea and Taiwan carried out effective land reform by redistributing private land rights without resorting to nationalization. It is argued that neither the notion of state ownership of land as practised in Singapore nor current improvements in the scope of Chinese land use rights explain the denial of economic value to land use rights. Key words: Land use rights, developmental state, land reform, property rights.